Organic syntheses greenness assessment with multicriteria decision analysis. Issue 23 (10th November 2021) - Tobiszewski, Marek; Przychodzeń, Witold; Bystrzanowska, Marta; Milewska, Maria J.
Abstract : Greenness metrics for comparative, comprehensive and simple assessment of organic syntheses processes. Abstract : Green chemistry requires a metrics system that is comprehensive by the criteria included and simple in the application at the same time. We propose the application of multicriteria decision analysis for comparative greenness assessment of organic synthesis procedures. The assessment is based on 9 criteria (the reagent, reaction efficiency, atom economy, temperature, pressure, synthesis time, solvent, catalyst and reactant) for which data points are easily extractable from synthesis protocols. The criteria are given weights by two experts to differentiate their relative importance. Two datasets are created, one of the procedures for benzoic acid synthesis, the second one of procedures for γ-valerolactone synthesis. In both cases, the greenest procedure is identified and the remaining ones are ranked according to their greenness. The proposed assessment procedure incorporates more assessment criteria than product/waster ratio mass-based metric and is much less tedious than the application of life-cycle assessment.